BENTUK HUBUNGAN HUKUM ANTARA BANK DENGAN NASABAH - Yanuarsi, Susi (Solusi, 2017)
This research uses normative jurisis method. research results: an important aspect in the legal relationship between the customer and the bank is an agreement between the two, which is usually made unilaterally by the bank. With the development of law and the entry of the law of the Anglo-Saxon State, the treaty as stipulated in the Indonesian Civil Code has been shifted. Formally the legal relationship between the bank and the customer was born since the signing of the application form or the opening of the customer's account at the bank. With the opening of the account, the legal relationship between the customer and the bank creates the rights and obligations of both parties.